Perancangan Knowledge Management System Model Choo Sense Making pada Pusat Teknologi Informasi - Dyah Retno Utari; Andy Rio Handoko (Prosiding SISFOTEK, 2019)
Pusat Teknologi Informasi on Indonesian Transaction Report and Analysis Center (INTRAC) have the task of implementing development and management of the processing system data and information system. Knowledge that is at Pusat Teknologi Informasi enough, but to walk slowly and tended to static. This research is focused on the knowledge that it had many shaped tacit and are stored in everyone, this research also to design a knowledge management who in accordance with their needs and can accommodate as well as turning knowledge from tacit become be explicit knowledge. Methodology this research done by means of observed and study literarur using framework tiwana model, as for the formation of knowledge using a Choo Sense Making Model that at the knowledge creation combined with a model SECI Nonaka. This research has produced a draft web base application knowledge management system that is easy to use in share knowledge through the application. The conclusion from this research that the use of Choo Sense Making Model is one of the model knowledge management system that was felt appropriate, where in the collection knowledge is to understand information is not only in internal environment but also external performed on stage sense making and in the formation the knowledge which was could be done through the approach to daily activities as discussion formal and informal or commonly called knowledge creation, so that the displacement of tacit become be explicit knowledge it is much easier.